Homoeopathic approach to Disruptive Mood Dysregulation Disorder (DMDD): Bridging Psychiatry and Homoeopathy - Nangia, Mohita; Arora, Nidhi (Indian Journal of Integrative Medicine, 2025)
Disruptive Mood Dysregulation Disorder (DMDD) is a childhood-onset psychiatric diagnosis, introduced in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) to curb the overdiagnosis of paediatric bipolar disorder. It is primarily characterised by chronic, severe irritability, frequent temper outbursts grossly disproportionate to the situation, and a persistently angry or irritable mood between outbursts. The aetiology of DMDD is multifactorial, involving a complex interplay of genetic predisposition, environmental influences, neurodevelopmental abnormalities, and psychosocial stressors. There are no definitive biomarkers, as the diagnosis relies on clinical observation and detailed case history. Conventional treatment typically includes cognitive-behavioural therapy (CBT), parent training, and in some cases, pharmacological interventions such as stimulants or antidepressants. However, alternative therapeutic modalities like Homoeopathy are gaining attention for their individualised, holistic approach. This article delves into the diagnostic criteria, differential diagnosis, clinical challenges, and various treatment options, with a special focus on the principles and application of homoeopathy in managing children diagnosed with DMDD.